Perancangan Sistem Cluster Server untuk Jaminan Ketersediaan Layanan Tinggi pada Lingkungan Virtual - Yudi Restu Adi; Oky Dwi Nurhayati; Eko Didik Widianto (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2016)
Computer based services are now used in various fields, such as business, health, and education. The objective is to improve the performance of the company, institution, or organization. Services and data are stored in a server machine. Therefore, the server machine becomes an important thing that supports the availability of services, beside network infrastructure and electricity. The server machine may have hardware failure or software crash. The server machine can be down because of a power failure, human error, or disaster. The server machine sometimes must be turned off for upgrades or maintenance purposes. When a server is down, services running on the server will stop and important data can be lost. The objective of this research is to build a server cluster system that supports high availability services and data integrity over a virtual environment. The result of this research is a cluster server system that supports high availability services over the virtual environment and guarantee data integrity using server virtualization Proxmox VE 3.4 on two computer machines, FreeNAS x86 9.2.1.9 as a NAS server, two units of the Cisco Catalyst 2960 switch, and DRBD for data synchronization.